The ADAPTASI ALAT UKUR SMARTPHONE ADDICTION SCALE-SHORT VERSION: DALAM BAHASA INDONESIA DENGAN EFA DAN CFA - Rama Zainul Aarifiin Firdaus; Muhamad Sandya Rachman; Khayyirah Syifa Nurkhalisah; Altair Ahsan; Aliyyah Nahda Putri Sinaga; Muhamad Arif Saefudin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Smartphone addiction has become an increasingly important psychological and behavioral issue because excessive smartphone use can interfere with individuals’ academic, social, physical, and emotional functioning. Although the Smartphone Addiction Scale–Short Version (SAS-SV) has been widely used in various countries, evidence for the Indonesian adaptation of the SAS-SV that examines its factorial structure through Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) using separate samples remains limited. This study aimed to adapt the SAS-SV into Indonesian and evaluate evidence of its construct validity and reliability. The adaptation process included forward translation, backward translation, synthesis of the translated versions, readability testing, and psychometric testing involving respondents in late adolescence to early adulthood. The data were randomly divided into EFA and CFA samples. The results showed that the data met the prerequisites for factor analysis. The EFA produced a three-factor structure, which was subsequently confirmed through CFA. The CFA model demonstrated good fit, and the total scale reliability showed adequate internal consistency, although the reliability of several factors still needs improvement. These findings indicate that the Indonesian version of the SAS-SV provides initial evidence of construct validity and adequate total-scale reliability for research purposes, with further testing recommended in larger and more diverse samples. ABSTRAK Kecanduan smartphone menjadi masalah psikologis dan perilaku yang semakin penting karena penggunaan smartphone yang berlebihan dapat mengganggu fungsi akademik, sosial, fisik, dan emosional individu. Meskipun Smartphone Addiction Scale–Short Version (SAS-SV) telah banyak digunakan di berbagai negara, bukti adaptasi SAS-SV dalam bahasa Indonesia yang menguji struktur faktorial melalui Exploratory Factor Analysis (EFA) dan Confirmatory Factor Analysis (CFA) pada sampel terpisah masih belum kuat. Penelitian ini bertujuan untuk mengadaptasi SAS-SV ke dalam bahasa Indonesia serta mengevaluasi bukti validitas konstruk dan reliabilitasnya. Proses adaptasi mencakup penerjemahan maju, penerjemahan balik, sintesis hasil terjemahan, uji keterbacaan, dan pengujian psikometrik terhadap responden berusia remaja akhir hingga dewasa awal. Data dibagi secara acak menjadi sampel EFA dan CFA. Hasil analisis menunjukkan bahwa data memenuhi prasyarat untuk analisis faktor. EFA menghasilkan struktur tiga faktor yang kemudian dikonfirmasi melalui CFA. Model CFA menunjukkan kesesuaian yang baik, dan reliabilitas total skala menunjukkan konsistensi internal yang memadai, meskipun reliabilitas pada beberapa faktor masih perlu ditingkatkan. Temuan ini menunjukkan bahwa SAS-SV versi bahasa Indonesia menunjukkan bukti awal validitas konstruk dan reliabilitas total yang memadai untuk digunakan dalam penelitian, dengan rekomendasi pengujian lanjutan pada sampel yang lebih besar dan beragam.